Boundary algebraic Bethe Ansatz for a nineteen vertex model with Uq [osp(2|2)(2)] symmetry. (27th September 2017) - Vieira, R S; Lima-Santos, A
Abstract: The boundary algebraic Bethe Ansatz for a supersymmetric nineteen vertex-model constructed from a three-dimensional representation of the twisted quantum affine Lie superalgebra U q [ o s p ( 2 | 2 ) ( 2 ) ] ≃ U q [ C ( 2 ) ( 2 ) ] is presented. The eigenvalues and eigenvectors of Sklyanin's transfer matrix, with diagonal reflection K -matrices, are calculated and the corresponding Bethe Ansatz equations are obtained. A numerical analysis for a small-length chain is also presented.